REDUPLICATION IN JAVANESE - I Dewa Putu Wijana (Masyarakat Linguistik Indonesia, 2021)
This paper aims at describing Javanese reduplication system with focus of attention on forms, functions, and grammatical meanings. By using data extracted from Javanese text books and ones of my own creation whose grammaticalty and acceptability are previously tested with several native speakers, through distributional method with its various technical analysis, the research found that Javanese reduplication can be classified into at least four linguistic forms. Those are full reduplication, partial reduplication, sound modification reduplication, and affix-combined reduplication. Javanese reduplication can either perform inflective or derivative function in relation to its potentiality to maintain and change the word identity. Finally, with regard to the grammatical meanings, Javanese reduplication at least can express eleven grammatical meanings, i.e. plurality, diversity, continuity, intensity, attenuation, reciprocity, artificiality, collectivity, rate, astonishment and contrast. Many of these grammatical meanings are context sensitive.